2018
DOI: 10.5194/aab-61-221-2018
|View full text |Cite
|
Sign up to set email alerts
|

Body condition status at mating affects gestation length, offspring yield and return rate in ewes

Abstract: Abstract. The present study was planned to determine the effect of ewe body condition score (BCS) and parities on fertility, return rate, gestation length, fecundity, litter size and lamb birth weight. Data were collected from 284 heads of ewes with first to fifth parity and raised at a state farm for three consecutive (2002)(2003)(2004) years. Teaser rams were used to monitor estrus twice daily in the morning and in the evening from September to October. BCSs and body weights (BWs) were recorded at mating and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Comparison of groups Q1 and Q4 revealed a higher proportion of transferable embryos (83.8 % vs. 53.2 %) and a lower proportion (9.6 % vs. 35.2 %) and count (0.6 % vs. 2.7 %) of degenerated embryos in the Q1 group (smallest change). In conclusion, the authors concluded that these results are in compliance with the idea that a lower BCS at the time of the first insemination is associated with fertility decline (Carvalho et al, 2014).…”
Section: Body Condition Of Cows From the Viewpoint Of Embryo Transfersupporting
confidence: 76%
See 1 more Smart Citation
“…Comparison of groups Q1 and Q4 revealed a higher proportion of transferable embryos (83.8 % vs. 53.2 %) and a lower proportion (9.6 % vs. 35.2 %) and count (0.6 % vs. 2.7 %) of degenerated embryos in the Q1 group (smallest change). In conclusion, the authors concluded that these results are in compliance with the idea that a lower BCS at the time of the first insemination is associated with fertility decline (Carvalho et al, 2014).…”
Section: Body Condition Of Cows From the Viewpoint Of Embryo Transfersupporting
confidence: 76%
“…Relationships between fertility and changes in body weight (BCS) were also the subject of the study by Carvalho et al (2014). The authors divided the cows at the postpartum period into four quartiles (Q) that presented changes (%) in body weight (Q1 indicates the smallest change; Q4 indicates the biggest change).…”
Section: Body Condition Of Cows From the Viewpoint Of Embryo Transfermentioning
confidence: 99%
“…Contrary to this, Mithuna et al (2015) reported that pre-partum concentrate supplementation (2 kg/d) had higher (24.33 vs. 28.00 kg) birth weight of buffalo calves as compared to nonsupplemented group. This contradiction might be due to fact that BCS of buffaloes during gestation and at calving was higher in present study, as the higher BCS at mating and during pregnancy results in higher birth weight and return rate compared to thin (Low BCS) animals (Cam et al 2018). Moreover, birth weight of calves in our study were also higher (ranged 30.3 to 33.5) compared to the study by Mithuna et al (2015) and close to the birth weight reported by Naqvi and Shami (1999) in Nili Ravi buffalo calves.…”
Section: Body Weight and Body Condition Scorescontrasting
confidence: 65%
“…This critical level can be reached through provision of adequate nutrition to ensure the appropriate LW/BCS at time of joining. Reproductive output of the ewe and progeny growth and survival can also be improved through improving LW/BCS at joining (Cam & Kirikci 2018), during early-mid (Paganoni et al 2014) and late pregnancy (Behrendt et al 2019).…”
Section: A L Batesmentioning
confidence: 99%